Experiences and Perceptions of Youth Out-Migration and Food Supply in Agricultural Households in Hohoe Municipality - Adom, F.K.E. (University of Ghana, 2017)
Looking at the increasing number of the youth migrating from the rural areas to an urban areas and bearing in mind the implications of rural-urban migration on the origin communities and destinations, this study sought to explore the challenges the rural folks face with regards to rural-urban migration particularly its effects on agricultural productivity. The objectives of the study were to: (i) describe the characteristics of a sample of household heads in the study area, (ii) find out about youth out-migration if any, (iii) examine communities ‘viewpoints about rural-urban migration among the youth, describe the food supply situation in the households and examine communities’ perception of the effects of youth out-migration on agricultural productivity. Adopting quantitative and qualitative research designs for complementarity, one hundred respondents from four agricultural communities were interviewed using a survey questionnaire. Four focus group discussions (FGDs) were held (2 female groups, 2 male groups). In each group there were eight (8) members. The findings for the study indicate that, about a third of the household heads interviewed fall between the ages of 55-59 years of age. Similarly in terms of gender, overwhelming majority (81%) of the heads of households interviewed were males. Majority (93%) of the household heads interviewed affirmed that there has been an out-migration of the youth annually and their preferred destination is outside the region, specifically Accra, Kumasi and Ashiaman. Most of the youth (68%) migrate because of lack of jobs in the area. On the views of the study respondents on the effects of youth out-migration on agricultural productivity, majority (94%) of the respondents also affirmed that migration of the youth affects agricultural productivity and to some extent food supply in the households. The study therefore recommended that since the basis of the youth out-migration is lack of job opportunities in the rural communities, government should set up cottage industries that would provide jobs for the rural youth in the Hohoe Municipality. By so doing, a number of the youth will not migrate to urban areas for non-existing jobs.
Keywords: Hohoe Municipality; Agricultural Households; Out-Migration; Food Supply; Youth